A Qualificação pela Certificação na Previdência Complementar - Avena, Lygia Maria (Revista ANPPREV de Seguridade Social, 2025)
Closed Supplementary Pension Plans are becoming increasingly important in Brazil to provide supplementary pensions to millions of participants and beneficiaries, provide them and their families with a more dignified living upon retirement, and act as a driver of economic development. In this capacity, it invests its significant reserves in various segments of the economy. It is also a pension alternative indicated by public policies, as is currently the case with supplementary pensions for civil servants. In this context, the greater complexity of the operations and legal relationships developed in the sector and the enormous challenges in the decision-making processes of managers, who have a fiduciary duty to seek to guarantee the contracted benefits, require these agents to be effectively trained to perform their duties well. To this end, the qualification of managers and their certification, under the supervision of the National Superintendence of Supplementary Pensions (Previc), are valuable instruments for achieving good governance practices and adequate risk management. This study addresses such aspects within Closed Supplementary Pensions, considering its institutional objectives and applicable regulations.